2014
DOI: 10.1016/j.crme.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cylinder proximity to the wall on channel flow heat transfer enhancement

Abstract: Heat-transfer enhancement in a uniformly heated slot mini-channel due to vortices shed from an adiabatic circular cylinder is numerically investigated. The effects of gap spacing between the cylinder and bottom wall on wall heat transfer and pressure drop are systemically studied. Numerical simulations are performed at Re = 100, 0.1 Pr 10and a blockage ratio of D/H = 1/3. Results within the thermally developing flow region show heat transfer augmentation compared to the plane channel. It was found that when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…They found that the cylinder wake altered significantly the thermal boundary layer, and wall heat transfer was increased when the temperature distributions became steeper. Mohesn et al [24] studied the effect of the cylinder which is close to the wall on heat transfer enhancement in channel flow. The results showed that the velocity and temperature distributions gradually tended to steady, the heat transfer and pressure drop gradually decreased when the distance from the cylinder to the bottom wall gradually became small.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the cylinder wake altered significantly the thermal boundary layer, and wall heat transfer was increased when the temperature distributions became steeper. Mohesn et al [24] studied the effect of the cylinder which is close to the wall on heat transfer enhancement in channel flow. The results showed that the velocity and temperature distributions gradually tended to steady, the heat transfer and pressure drop gradually decreased when the distance from the cylinder to the bottom wall gradually became small.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, reduction in chips size is a real challenge for designing efficient cooling systems with limited space in which to reject generated heat [1][2][3][4]. One of the promising systems by which high performance heat rejection can be achieved is micro and mini-scale systems, such as micro-channel heat exchangers and heat sinks [5][6][7][8][9]. They are different from traditional channels, and can be classified according to their associated hydraulic diameters, D h , [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The present work is focused on cylindrical or rib-based structures, which have received some recent attention. A 2D numerical study by Cheraghi et al [6] investigated the impact of the position of an adiabatic cylinder in a uniform micro-channel. They used fixed heat flux applied to the wall sides, Reynolds number of 100 and the Prandtl number ranged from 0.1 to 1.…”
Section: Introductionmentioning
confidence: 99%
“…A 2D numerical study utilized smooth channel with fixed heat flux applied to the wall sides having an adiabatic cylinder inside which was perpendicular to the laminar flow direction with Reynolds number of 100and Prandtl number ranging from 0.1 to 1 [3]. The authors have investigated the influence of the distance between the base and the top of the channel as they This is the accepted manuscript of an article published in International Communications in Heat and Mass Transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore there is a need to improve cooling systems by decreasing their size and weight to micro-and mini-scale systems, such as micro-channel heat exchangers and heat sinks [2], while simultaneously increasing the efficiency to meet this development [3]. Mini-and micro-channels are different from traditional channels, and can be classified according to their associated hydraulic diameters, Dh, [4][5][6] as presented in table 1.…”
Section: Introductionmentioning
confidence: 99%